Asuhan Kebidanan Pada Bayi Ny.I Di TPMB Rupi′Ah Suparman - Belandina Betty; Hanna Harnida; Andi Jayawardhana (2023)
Providing midwifery care to BBL and neonates using a midwifery management approach. Research method The midwifery care model used in this research with midwifery care management according to Hellen Varney, includes assessment subjective and objective, identification of problem diagnoses, identification of potential problem diagnoses, identification of immediate needs, planning (intervention), implementation (implementation), and evaluation. As well as monitoring visits in the form of SOAP. The results of midwifery care for newborns and neonates diagnosed the condition of Mrs. I's newborn and neonate within normal limits and there were no complications or gaps between theory and diagnosis. The care was in accordance with midwifery service standards.